Back Cover: Unsymmetrically Substituted Donor–π–Acceptor‐Type 5, 15‐Diazaporphyrin Sensitizers: Synthesis, Optical and Photovoltaic Properties (ChemPlusChem 5/2017). Issue 5 (10th March 2017) - Omomo, Satoshi; Tsuji, Yukihiro; Sugiura, Kenichi; Higashino, Tomohiro; Nakano, Haruyuki; Imahori, Hiroshi; Matano, Yoshihiro
Abstract : The cover picture shows a stepwise synthesis of unsymmetrical β‐substituted 5, 15‐diazaporphyrins (DAPs). Donor–π–acceptor‐type DAPs exhibit excellent light‐harvesting properties over the whole visible range. The cell performance of dye‐sensitized solar cells made with these DAPs is the highest reported for such sensitizers. Details are given in the Full Paper by Y. Matano and co‐workers onpage 695 in Issue 5, 2017 (DOI:10.1002/cplu.201700051 ).